2014
DOI: 10.1002/glia.22704
|View full text |Cite
|
Sign up to set email alerts
|

Gender influence on schizophrenia‐relevant abnormalities in a cuprizone demyelination model

Abstract: The aim of this study was to determine whether early demyelination can impact behavior in young adulthood. For this purpose, albino Wistar rats of either sex were exposed to cuprizone (CPZ) in two different intoxication protocols: one group was intoxicated before weaning (CPZ-BW), from postnatal day 7 (P7) to P21, through maternal milk, whereas the other group was intoxicated after weaning (CPZ-AW), from P21 to P35. After treatment, rats were returned to a normal diet until P90 when behavioral studies were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The effect of cuprizone has been tested in other preclinical models of anxiety, including open field and light-dark tests. The majority of papers using the open field test showed that a cuprizone diet caused increased anxiety with decreased time or distance in the centre zone [ 55 , 70 , 72 , 75 , 76 , 79 , 80 , 81 , 82 ]; conversely, whereas, others found increased time in the centre [ 25 , 83 ] or no difference [ 35 , 84 ]. Using the light-dark test, mice fed a cuprizone diet spent less time in the light box, which is correlated to increased anxiety [ 70 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of cuprizone has been tested in other preclinical models of anxiety, including open field and light-dark tests. The majority of papers using the open field test showed that a cuprizone diet caused increased anxiety with decreased time or distance in the centre zone [ 55 , 70 , 72 , 75 , 76 , 79 , 80 , 81 , 82 ]; conversely, whereas, others found increased time in the centre [ 25 , 83 ] or no difference [ 35 , 84 ]. Using the light-dark test, mice fed a cuprizone diet spent less time in the light box, which is correlated to increased anxiety [ 70 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some labs have also reported intoxicating their mice by oral gavage of solubilized cuprizone. While sex, genetic background, and age of the animals have been identified as important variables for the reproducibility and the extent of cuprizone-induced pathological changes [99][100][101], "weight" as a critical variable for reliable and consistent demyelination has just recently been systematically addressed. In a recent work, we have investigated this issue, and were able to show that animal weight is an important variable for reliable cuprizone-induced demyelination [102].…”
Section: Animal Weightmentioning
confidence: 99%
“…Several models have examined how demyelination might induce the hyperdopaminergic state found in schizophrenic patients, involving a misbalance in glutamate . Altered myelination could correlate with an aberrant wiring network, which in turn triggers alterations in dopamine levels . Our results suggest that the timing of demyelination significantly influences the development of schizophrenia‐relevant behavior, particularly in adult males.…”
Section: Discussionmentioning
confidence: 74%